1998
DOI: 10.1103/revmodphys.70.929
|View full text |Cite
|
Sign up to set email alerts
|

Quantum diffusion of muons and muonium atoms in solids

Abstract: The diffusion of muons and muonium through solids has been studied over many years using the technique of spin relaxation. At low temperatures, the motion is due to tunneling between lattice sites, and the competition between tunneling rates and decoherence rates is important in determining the dynamics. Coherent propagation is seen in superconductors and insulators at low temperature where dissipation is small. At higher temperatures the motion undergoes a crossover from bandlike propagation to incoherent hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 170 publications
7
62
1
Order By: Relevance
“…Moreover, at strong coupling there is an additional transition of the attractive polaron into a bound molecular state [34]. We will only discuss the regime of weak impurityBose interactions which satisfy the condition (6) and are captured by our Fröhlich model (3), (4), with parameters (5).…”
Section: Polaron Ground State In Becmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, at strong coupling there is an additional transition of the attractive polaron into a bound molecular state [34]. We will only discuss the regime of weak impurityBose interactions which satisfy the condition (6) and are captured by our Fröhlich model (3), (4), with parameters (5).…”
Section: Polaron Ground State In Becmentioning
confidence: 99%
“…Our treatment of the impurity-BEC system ignores the phenomenology of strong-coupling physics, e.g., near a Feshbach resonance [34], which lies beyond the parameter range (6). The model (3), (4), with parameters (5), in its regime of validity, constitutes a generalized Fröhlich model of polarons in ultracold BECs [29][30][31][32].…”
Section: Microscopic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the concept of localization by disorder has been introduced primarily in order to describe the electronic transport properties of condensed matter, it may also be applied to the quantum dynamics of heavier particles, whether charged or neutral [5,1]. Recent experimental results for positive muons as well as for muonium atoms clearly indicated that interaction with crystal excitations and crystal disorder dramatically changes the nature of tunneling dynamics for particles~200 times heavier than the electron.…”
Section: Introductionmentioning
confidence: 99%
“…This happens in insulators and semiconductors, while in metals we deal with the «bare» muon. Because of the unique mass of the muon one can hardly mention any other example where quantum diffusion was observed in such a wide temperature range as for m + and Mu [1]. The other reason for the success of the quantum diffusion study using muons is the sensitivity of the muon spin relaxation (mSR) techniques (see e.g.…”
Section: Introductionmentioning
confidence: 99%